2007
DOI: 10.1111/j.1743-6109.2007.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Vardenafil in East Asian Men with Erectile Dysfunction

Abstract: Introduction Previous clinical studies assessing the efficacy and safety of vardenafil, an oral phosphodiesterase type 5 inhibitor, in men with erectile dysfunction (ED) have consisted mostly of Caucasian patients. Aim The aim of this article is to describe the efficacy and safety of vardenafil in men of East Asian ethnicity with ED. Methods Data were pooled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
7
13
0
Order By: Relevance
“…In the present study, which contained a high percentage of Asian subjects (43.8%), vardenafil treatment was associated with favourable outcomes for effectiveness, safety and relationship quality. This echoes the findings of a previous study, which demonstrated the excellent efficacy and tolerability of vardenafil in a population of exclusively East Asian men [30]. There are some limitations to this study.…”
Section: Patientssupporting
confidence: 88%
“…In the present study, which contained a high percentage of Asian subjects (43.8%), vardenafil treatment was associated with favourable outcomes for effectiveness, safety and relationship quality. This echoes the findings of a previous study, which demonstrated the excellent efficacy and tolerability of vardenafil in a population of exclusively East Asian men [30]. There are some limitations to this study.…”
Section: Patientssupporting
confidence: 88%
“…For patients experiencing ED, first-line therapy typically includes one or more trials with a phosphodiesterase-5 inhibitor (PDE5i). These agents result in successful penetrative intercourse in the order of 80% [5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 98%
“…36 Treatment with vardenafil produced significant improvement in the main efficacy measures of IIEF-EF score and SEP2 and SEP3 as well as the GAQ. The efficacy [31][32][33][34][35][36][37][38][39][40][41][42][43][44] Prevalence and management of ED in Asia K Park et al 547…”
Section: Efficacy and Safety Of Sildenafilmentioning
confidence: 99%
“…These included four RCTs of sildenafil, [31][32][33][34] two RCTs of vardenafil, 35,36 four RCTs of tadalafil, [37][38][39][40] two RCTs of udenafil 41,42 and two RCTs of mirodenafil. 43,44 The efficacy and safety of two novel PDE-5 inhibitors, mirodenafil and udenafil, were evaluated only in Korean men.…”
Section: Medical Treatment Of Ed In Asiamentioning
confidence: 99%
See 1 more Smart Citation